Elephant diet at the edge of the Fynbos Biome, South Africa - Antoni Milewski (Pachyderm)
Reviews observations of two forest guards who from 1990 to 2000 noted the diet and preferred foods of Knysna elephants, in the Fnybos Biome along the southern coastal region of South Africa. All plants eaten by five elephants, the last three known native animals and two introduced juveniles, were noted 'this is the first evidence that elephants routinely eat the nutrient-poor, heathy shrubs and wiry grasslike plants of the fynbos'. The native animals spent 90% of their time in the forest, but when released in 1994 the introduced juveniles only spent 2 months in this habitat. From then on they spent: 80% in fynbos and rough pasture, 10% in patchy forest, 5% in mature tree plantations, and less than 5% near vegetable/croplands which they raided. 11 species of forest trees and shrubs were eaten, Rapanea, Pterocelastrus, and Ilex seemed to be preferred. The introduced juveniles mainly ate bark when in the forest. Most of the common genera of shrubs and grasslike plants of the fynbos were eaten, but most herbaceous plants were ignored. Exotic trees in plantations were occasionally damaged for their bark and many Acacia, particularly A mearnsii were broken down, and bark, pods and leaves eaten. The animals sometimes excavated and ate tubers and rhizomes of herbaceous plants such as Iridaceae and bracken fern (Pterodium) but did not eat soil. The author notes the complementary diets elephant may have with other indigenous herbivores, and discusses the commonly held view that the Knysna habitat lacks trace elements. Observations suggest elephant could be maintained in the Fynbos Biome, and their presence in this area might be useful in controlling invasive exotic plants.